The functional identification and evaluation of endophytic bacteria sourced from the roots of tolerant Achyranthes bidentata to overcome monoculture problems of Rehmannia glutinosa - Zeng, Chunli; Liu, Yazhou; Zhang, Bianhong; Zhang, Chenjing; Li, Niu; Ji, Leshan; Lan, Chaojie; Qin, Bin; Yang, Yuncheng; Wang, Juanying; Chen, Ting; Fang, Changxun; et al. (Frontiers in Microbiology, 2024)
The isolation and identification of plant growth-promoting endophytic bacteria (PGPEB) from Achyranthes bidentata roots have profound theoretical and practical implications in ecological agriculture, particularly as bio-inoculants to address challenges associated with continuous monoculture. Our research revealed a significant increase in the abundance of these beneficial bacteria in A. bidentata rhizosphere soil under prolonged monoculture conditions, as shown by bioinformatics analysis.Subsequently, we isolated 563 strains of endophytic bacteria from A. bidentata roots.Functional characterization highlighted diverse plant growth-promoting traits among these bacteria, including the secretion of indole-3-acetic acid (IAA) ranging from 68.01 to 73.25 mg/L, phosphorus and potassium solubilization capacities, and antagonistic activity against pathogenic fungi (21.54%-50.81%). Through 16S rDNA sequencing, we identified nine strains exhibiting biocontrol and growth-promoting potential.significantly increased root biomass by 48.19% in A. bidentata and 27.01% in replanted Rehmannia glutinosa. These findings provide innovative insights and strategies for addressing continuous cropping challenges, highlighting the practical promise of PGPEB from A. bidentata in ecological agriculture to overcome replanting obstacles for non-host plants like R. glutinosa, thereby promoting robust growth in medicinal plants.